Formation of Compressive Residual Stress by Face Milling Steel AISI 1045 - Al-Khazraji, Ahmed Naif; Al-Rabii, Samir Ali; Al-Fahadawy, Samir Zidan (Al-Khwarizmi Engineering Journal, 2017)
Abstract Machining residual stresses correlate very closely with the cutting parameters and the tool geometries. This research work aims to investigate the effect of cutting speed, feed rate and depth of cut on the surface residual stress of steel AISI 1045 after face milling operation. After each milling test, the residual stress on the surface of the workpiece was measured by using X-ray diffraction technique. Design of Experiment (DOE) software was employed using the response surface methodology (RSM) technique with a central composite rotatable design to build a mathematical model to determine the relationship between the input variables and the response. The results showed that both the feed rate and the cutting speed are the significant factors controlling the surface residual stress, while the depth of cut had no influence. A quadratic empirical model was developed with a 95% confidence level, and a good agreement was found between the experimental and predicted results. A numerical optimization was then conducted through DOE program to find the optimum surface residual stress at the optimum cutting parameters, depending on the maximum desirability obtained. The optimum compressive surface residual stress (-224.361 MPa) was found at cutting speed of 69.2 m/min, feed rate of 0.4 m/min and depth of cut of 0.4 mm. Keywords: Face milling, Cutting parameters, Steel AISI 1045, Residual stresses, XRD; DOE, RSM, Modeling and Numerical optimization.